Patients’ Satisfaction Towards Doctor’s Behaviour and Environment of Outpatient Department of Shaikh Zayed Hospital Lahore - Fatima Kausar Nawaz, Muneeba Afzal, Rabia Khalid, Mahek Zeeshan, Ayesha Afzal, Amna Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients’ satisfaction is defined as a subjective evaluation of the service received against the individual’s expectations. Patients’ satisfaction should be measured frequently as it is the important indicator of quality in health care and also because there is still room for improvement in quality of health care. Objective: The aim of this research is to determine patients’ satisfaction in reference to doctor’s behavior and environment of the out-patient department at the tertiary care teaching hospital. Materials and Methods: Study was carried out in OPD of Sheikh Zayed Hospital using a pretested questionnaire with 320 samples from January 2022 to March 2022, selected by systemic random sampling technique. The data was analyzed using SPSS version 21.00. Data was presented using figure and tables and described using frequencies and percentages. Result: Patients expressing satisfaction were 68.4% while remaining 31.5% were dissatisfied with their OPD experience. Overall behavior of doctor towards patients was satisfying while the environmental structure of OPD showed some flaws. Mean consultation time given by doctor was found to be 5.78±4.28 minutes. And 53.1% of the patients waited for more than 45 minutes. Conclusion: The findings of this survey must be used to bring improvement. Loopholes found in environmental structure should be addressed timely. Satisfaction level can further be improved and brought to the level of developed countries.